Cytokeratin-positive Fibroblastic Reticular Cell Tumor With Follicular Dendritic Cell Features: A Case Report and Review of the Literature. (April 2015) - Goto, Naoe; Tsurumi, Hisashi; Takami, Tsuyoshi; Futamura, Manabu; Morimitsu, Kasumi; Takata, Katsuyoshi; Sato, Yasuharu; Yoshino, Tadashi; Adachi, Seiji; Saito, Koshiro; Yamakawa, Mitsunori
Abstract : Fibroblastic reticular cell (FRC) neoplasms, which are one of the histiocyte tumor types, are very rare. Here we report a cytokeratin (CK)-positive FRC neoplasm having features of follicular dendritic cells in a 54-year-old woman with right axillary lymph node swelling. The resected lymph node showed multiple nodular aggregations simulating and replacing normal follicles. The tumor cells had a uniform, large and oval to polygonal shape, abundant cytoplasm, and various sizes of nuclei with central eosinophilic nucleoli and coarse nuclear chromatin. They were positive for CK AE1/AE3+CAM5.2, CK7, tenascin C, l-caldesomone, and CD21, weakly positive for S100, and negative for CD1a. Ultrastructurally, the tumor cells had long interdigitating microvillus-like cell processes and oval to elongated vesicular nuclei. In addition, the intercellular spaces contained accumulations of collagen, and some tumor cells had desmosomal-like junctions. These findings suggest that the present case is a CK-positive FRC tumor with follicular dendritic cell features.